Optimalisasi Fungsi Staffing Kepala Ruangan dalam Penjadwalan Waktu Kerja dan Istirahat untuk Mengurangi Workload pada Perawat Pelaksana di Masa Pandemi - Maria Franciska Vianney Boro; La Ode Abd Rahman; Nurdiana Nurdiana (Journal of Telenursing (JOTING), 2021)
This study aims to identify the optimization of the staffing function by the head of the room in the division of work and rest time to reduce nurses' workload in the inpatient unit. The research method used is a pilot project which starts from identifying problems related to the implementation of nursing management functions in hospitals, analyzing problems, prioritizing issues, preparing plans of action, implementing, evaluating structures and discussing based on literature reviews. The results of the study illustrate that the organizing function and actuating function (66%) are not optimal, while the planning function (53%), staffing (63%) and controlling (63%) are optimal. The performance category shows a description of the nurse's workload at a low percentage. The temporal demand category has 74%, followed by the mental demand category 68%, frustration level 63%, physical demand 58% and effort 53%. In conclusion, the application of the scheduling function of the head of the room at Hospital X is not optimal and still requires implementation following field conditions. Keywords: Workload, COVID-19, Employment Function, Rest Time